Prevalence and predictors of Implanon uptake in Ugu (Ugu North Sub District) 2016/17 - Anudha Moodley; Ozayr Mahomed (South African Family Practice, 2019)
Background: The contraceptive implant (Implanon) has been recognised as one of the most effective family planning methods and is a healthier choice for women in Africa due to its efficacy and convenience. Despite the evidence of effectiveness and safety of the implant, the actual uptake for Implanon use in the Ugu district of KwaZulu-Natal is relatively low. The aim of the study was to determine factors associated with Implanon uptake in Ugu North Sub District 2016/17. Methods: An observational cross-sectional study with an analytical component using self-administered questionnaires to collect information from 385 participants using randomised systematic sampling was conducted at family planning clinics at GJ Crookes Hospital and seven surrounding primary health care clinics. The chi-square test and multivariate logistic regression was used to determine associations. Results: Some 16% (n = 60) of the participants utilised Implanon. Despite having the correct knowledge 65.7% (n = 220) were not willing to use Implanon if it were offered. In addition, 55% of participants (n = 177) believed Implanon had more side effects. Parity ( 4 children) was found to be a statistically significant protective factor against (p 0.05) Implanon uptake. Conclusion: Implanon is a highly unattractive method of contraception for women residing in the Ugu North Sub District. Fear of side effects and invasive method of insertion were identified as the major barriers to Implanon use. Education and increased patient awareness are strategies to increase the desirability and uptake of Implanon.